Symulacja kapitalistycznej gospodarki-świata: Europa Universalis IV - Sitek, Wojciech (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
Grand strategy wargames and 4X productions are often viewed as educational tools that develop logical thinking skills. In reality, however, they undermine the user’s critical thinking. They pursue contemporary political agendas under the guise of historical education. Grand strategy wargames promote narratives that benefit big capital, while their “historicity” reinforces current economic activities. An analysis of Europa Universalis IV, using the theoretical framework proposed by Immanuel Wallerstein, reveals how the development of capitalism is naturalized, social inequalities are normalized and violence is legitimized. Underneath the narrative of four centuries of history, the creators from the Paradox Development Studio are hiding the interests of the contemporary beneficiaries of capitalism.